Particle Swarm Optimization-Based MPPT Performance of a Minimum Phase Bipolar Converter - Kumar P.; Barnawal P.J.; Lal V.N.; Singh R.K. (My University, 2025)
This paper analyzes the performance of Particle Swarm Optimization (PSO) based maximum power point tracking for a minimum phase bipolar converter (MPBC). The proposed MPBC can supply bipolar dc output. To develop the proposed MPBC, the Cuk and the SEPIC converters are integrated along with circuit modifications in both to achieve minimum phase behavior. The minimum phase behavior of MPBC enables it to achieve improved bandwidth and phase margin simultaneously and therefore provides better dynamic performance with photovoltaics (PV). Naturally, the variations in solar irradiance are intermittent in nature. Further, the presence of foreign elements and objects blocks the PV cell and creates a partial shading condition (PSC). The conventional algorithm such as P&O and INC is not suitable for PSC and therefore PSO is used for the MPPT operations. The improved characteristics of the proposed MPBC provide an easy platform to integrate PSO with it and provide better dynamic performance for various transient conditions. An MPBC is designed and tested for various dynamic conditions and operation characteristics of the proposed MPBC with PSO are captured for the analysis. © 2023 IEEE.